2019
DOI: 10.1016/j.schres.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Brain insulin resistance and altered brain glucose are related to memory impairments in schizophrenia

Abstract: Memory is robustly impaired in schizophrenia (SZ) and related to functional outcome. Memory dysfunction has been shown to be related to altered brain glucose metabolism and brain insulin resistance in animal models and human studies of Alzheimer's disease. In this study, differences in brain glucose using magnetic resonance spectroscopy (MRS) and blood Extracellular Vesicle (EV) biomarkers of neuronal insulin resistance (i.e. Akt and signaling effectors) between SZ and controls were investigated, as well as wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 74 publications
5
36
0
Order By: Relevance
“…Interestingly, modifications in the concentration of markers of insulin resistance were also found in EVs derived from the plasma of patients suffering schizophrenia. By magnetic resonance spectroscopy an increase of glucose concentration in the brain of these individuals was noticed [272]. Moreover, it was shown that the increase of insulin resistance and of glucose concentration are related to memory deficit [272].…”
Section: Evs In Neuropathologymentioning
confidence: 98%
“…Interestingly, modifications in the concentration of markers of insulin resistance were also found in EVs derived from the plasma of patients suffering schizophrenia. By magnetic resonance spectroscopy an increase of glucose concentration in the brain of these individuals was noticed [272]. Moreover, it was shown that the increase of insulin resistance and of glucose concentration are related to memory deficit [272].…”
Section: Evs In Neuropathologymentioning
confidence: 98%
“…Extracellular vesicles contain cargo that reflects the content of the vesicle's cellular origin, providing a novel avenue for probing intracellular signaling processes including neuroinflammatory pathways that are putatively implicated in neuropsychiatric disorders. This methodology has been used to directly assess neuronal inflammatory biomarkers in mild traumatic brain injury [25,26], as well as biomarkers from other pathways in disparate conditions, such as Alzheimer's disease (AD) and schizophrenia [27,28]. In addition, NEVs have been used as a source of biomarkers that predict neuronal-specific molecular target engagement and response to experimental treatments in clinical trials (e.g., in Parkinson's disease [21], AD [29], and cancer [30]), revealing concerted engagement of entire signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is associated with the inability of target tissues to increase glucose uptake in response to insulin [52]. Insulin resistance of brain tissues can reduce glucose levels in the brain by glucose-transporter-dependent pathways (among others, GLUT4), which together cause disturbed neurotransmission and disease progression [53]. Obese patients treated with atypical neuroleptics, in addition to insulin resistance, develop an additional phenomenon of lipotoxicity, leading to an increase in the level of free fatty acids (FFA) in the plasma, which is explained by their competition with glucose as oxidative substrates [54].…”
mentioning
confidence: 99%